A Moderated Mediation Model of the Relationship Between Primary and Secondary School Teachers’ Digital Competence and Online Teaching Behavior - Li, Wei; Gao, Wenyang; Fu, Weidong; Chen, Yiyan (Frontiers in Education, 2021)
A growing body of work has been devoted to studying teachers' digital competence, but not much is known about how teachers' digital competence affects online teaching behavior. Guided by the technological pedagogical content knowledge (TPACK) framework, this study investigated how teachers' digital competence affects online teaching behavior based on Chinese primary and secondary teachers (N = 1,833). The results indicated that the level of online teaching intentions mediated the relationship between teachers’ digital ability and online teaching behavior. Students’ learning difficulties in online learning moderated the relationship between teachers’ digital competence and the intention to use online teaching, such that the relationship became stronger as students’ online learning difficulties decreased. Similarly, the indirect relationship between teachers’ digital competence and online teaching behavior was stronger at decreased levels of students’ online learning difficulties. The findings contribute to a better understanding of the impact of teachers' digital competence on online teaching behavior.